Linguistic Human Rights and Trilingual Educational Policy of Nepal - Paneru, Narayan (Journal of Durgalaxmi, 2022)
Resource-based approach and right-based approach in education are the two contending issues among the academicians who have their own opinions about whether to ensure individuals’ linguistic human rights or to treat language as a communication resource. However, this article aims to justify the suitability of the right-based approach in the trilingual educational policy of Nepal by providing arguments from cultural, social, economic, and educational perspectives. Firstly, it introduces right-based and resource-based approaches in education. Secondly, it concentrates on how this approach relates to present Nepal’s trilingual educational policy in practice. Finally, it advocates for the rigorous implementation of this policy of the government of Nepal for the cultural, social, economic and academic development of the learners and conservation of their linguistic human rights. It further explicates the role of translanguaging, bilingualism and multilingualism as some of the strategies or approaches that can be used according to the local context and needs of the learners.